2015
DOI: 10.1111/apv.12085
|View full text |Cite
|
Sign up to set email alerts
|

Making REDD+ pay: Shifting rationales and tactics of private finance and the governance of avoided deforestation in Indonesia

Abstract: This paper presents an analysis of changing rationales and tactics among actors engaged in mobilising private finance for Indonesia's emergent Reducing Emissions from Deforestation and Forest Degradation (REDD+) programme. Despite limited flows of private finance so far, private sector actors have been responsible for a great deal of development and innovation in the forest carbon sector in Indonesia, and have thus played -and continue to play -an important part in shaping the country's REDD+ programme. Drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…As a part of REDD+ readiness in Indonesia, various policy-related and project-based pilot activities have been implemented (Dixon & Challies, 2015;McNeill, 2015). Because these initiatives of project-level REDD+ under complex socioeconomic conditions will be common challenges in Indonesia, this study examined how identification of agents and drivers of deforestation through socioeconomic surveys can be utilized for instituting the REDD+ activities design in readiness phase.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of REDD+ readiness in Indonesia, various policy-related and project-based pilot activities have been implemented (Dixon & Challies, 2015;McNeill, 2015). Because these initiatives of project-level REDD+ under complex socioeconomic conditions will be common challenges in Indonesia, this study examined how identification of agents and drivers of deforestation through socioeconomic surveys can be utilized for instituting the REDD+ activities design in readiness phase.…”
Section: Introductionmentioning
confidence: 99%
“…The case of Harapan most clearly illustrates the difficulties in securing sufficient long-term funding, an issue both recognized in the literature (Phelps et al 2011, Streck 2012, Busch 2013, Dixon and Challies 2015, Vijge et al 2016) and widely reported by respondents from our research outside of these three case studies. In an experience similar to what has been reported in the literature (UN-REDD Programme 2013) and by many other of our interviewees, project organizers initially thought that funding could be secured through the carbon market, the Norway money, or the U.N. REDD+ program itself, but later when financing did not materialize, funding alternatives had to be sought.…”
Section: As One Stakeholder Put Itmentioning
confidence: 60%
“…One particularly striking example can be found with the United Nations' REDD+ Pilot Project in Indonesia, which lists a lack of funding as one of the two main reasons for its eventual demise (UN REDD Programme 2013). Although all of the projects included in this case study had secured some level of funding, the process of obtaining long-term and sufficient funding was one of the most frequently mentioned challenges by the stakeholders included in our fieldwork (Dixon andChallies 2015, Well andCarrapatoso 2016).…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…This article is part of a wider study exploring the political ecology of rainforest carbon financing (e.g. McGregor et al ; Astuti & McGregor ; Dixon & Challies ; Howson & Kindon ; McGregor et al ; Weaver ).…”
Section: Introductionmentioning
confidence: 99%